Five-factor model of personality and Parkinson's Disease: a systematic review - Thayná Lais de Souza Arten; Amer Cavalheiro Hamdan (Brazilian Society of Geriatrics and Gerontology, 2023)
Some studies have associated Parkinson's disease with specific personality traits. We aimed to analyze personality profiles in Parkinson's disease based on the Five-Factor Model, using the following 3 instruments as parameters: NEO Personality Inventory, revised NEO Personality Inventory, and NEO Five-Factor Inventory. A systematic review was conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses. The PsycINFO, PubMed, Scopus, and Web of Science databases were searched. The initial search resulted in 232 studies, and 11 studies were selected for full-text review. The personality traits most commonly associated with Parkinson's disease were high neuroticism and low extraversion and conscientiousness. These results cannot be attributed only to Parkinson's disease because other associated diseases were present in the included studies. Evidence from these studies is insufficient to state that there is a typical personality profile associated with Parkinson's disease, given that this profile is nonspecific and found in many psychopathological disorders that differ considerably from each other. This study was registered with PROSPERO (registration number CRD42021271526).